Impelemntasi Faktor-Faktor yang Memengaruhi Kontraktor Utama dalam Keputusan Pemilihan Subkontraktor dan Supplier - Aditya Martiano (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to find out and analyze how the decision to select subcontractors and suppliers in construction projects is actually carried out, find out and analyze what factors are the benchmarks that influence the main contractors to make decisions on appointing subcontractors and suppliers, find out and analyze to what extent these factors The factors that influence the decision to select subcontractors and suppliers were implemented in the construction project. The object of this research is theconstruction project of the Wastewater Disposal Installation (IPAL) in Pekanbaru City, Riau which was carried out by PT. Adhikarya as the main contractor. The subject of this research is PT. Adhikarya as the main contractor, subcontractor and supplier involved in the supply chain of this project. This research was conducted with descriptive qualitative methods and triangulation data collection methods (interviews, observations, and documentation). The results of this study indicate that the factors that are used as benchmarks for making decisions on the appointment of subcontractors and suppliers by the main contractor in the Pekanbaru City Wastewater Disposal Installation (IPAL) project by PT. Adhikarya are company performance, company achievements, resources, information, marketing, and cooperative relationships. and from the results of comparisons with other PT. Adhikarya construction projects, the factors used are mostly the same, only there are differences in the aspects of work and materials depending on the needs and conditions of each project which is different.